2010
DOI: 10.1111/j.1460-9568.2010.07331.x
|View full text |Cite
|
Sign up to set email alerts
|

Tonic GABAergic control of mouse dentate granule cells during postnatal development

Abstract: The dentate gyrus is the main hippocampal input structure receiving strong excitatory cortical afferents via the perforant path. Therefore, inhibition at this 'hippocampal gate' is important, particularly during postnatal development, when the hippocampal network is prone to seizures. The present study describes the development of tonic GABAergic inhibition in mouse dentate gyrus. A prominent tonic GABAergic component was already present at early postnatal stages (postnatal day 3), in contrast to the slowly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 90 publications
(233 reference statements)
3
26
0
Order By: Relevance
“…To do so, we applied NNC-711 (5 M), a specific inhibitor of GABA transporter 1 (GAT-1), to block GABA reuptake (Suzdak et al 1992). Consistent with previous reports in hippocampus (Holter et al 2010;Stell and Mody 2002), NNC-711 shifted I hold to more negative values in six of six cells (⌬I hold ϭ Ϫ19.05 Ϯ 5.96 pA, ⌬CD ϭ Ϫ0.24 Ϯ 0.056 pA/pF; 1-sample t-test, P ϭ 0.0080 vs. baseline; Fig. 1, C and G).…”
Section: Tonic Inhibitory Transmission Is Present In Cea Neuronssupporting
confidence: 59%
“…To do so, we applied NNC-711 (5 M), a specific inhibitor of GABA transporter 1 (GAT-1), to block GABA reuptake (Suzdak et al 1992). Consistent with previous reports in hippocampus (Holter et al 2010;Stell and Mody 2002), NNC-711 shifted I hold to more negative values in six of six cells (⌬I hold ϭ Ϫ19.05 Ϯ 5.96 pA, ⌬CD ϭ Ϫ0.24 Ϯ 0.056 pA/pF; 1-sample t-test, P ϭ 0.0080 vs. baseline; Fig. 1, C and G).…”
Section: Tonic Inhibitory Transmission Is Present In Cea Neuronssupporting
confidence: 59%
“…A powerful tonic GABAergic signaling has been described in granule cells of the dentate gyrus already at P3 (Holter et al, 2010). Using subunit-specific pharmacological modulators, it has been demonstrated that, as in adults (Glykys et al, 2008), this conductance is mediated by a5 and d subunits containing extrasynaptic GABA A receptors.…”
Section: Early In Postnatal Development Tonic Gabaergic Currents Difmentioning
confidence: 99%
“…The relative contribution of receptors containing α5-subunits decreases with age, while that of receptors containing δ-subunits increases, indicating that as in principal cells the expression of d subunits is developmentally regulated. The increased expression of d subunits parallels that of tonic conductance that reaches its maximum during the second postnatal week and then declines (Holter et al, 2010). Surprisingly, unlike immature CA1 and CA3 principal cells (Marchionni et al, 2007), this conductance exerts mainly an inhibitory effect via ashunting inhibition.…”
Section: Early In Postnatal Development Tonic Gabaergic Currents Difmentioning
confidence: 99%
“…As discussed above, in particular the different subunit composition of GABA A receptors or distinct distribution and transport modes of GATs can contribute to these age-dependent effects. For instance in the rodent hippocampus α 5 subunit expression (Ramos et al, 2004) and, correspondingly, tonic GABAergic currents (Holter et al, 2010) are up-regulated during the first postnatal week. Due to the depolarizing GABAergic responses during these stages (Ben-Ari et al, 2012), these tonic GABAergic currents increase the excitability of the immature hippocampus (although GABAergic responses can mediate shunting inhibition even at depolarizing potentials; Kolbaev et al, 2011).…”
Section: Tonic Currents Regulate Excitation After Gabaergic Synaptogementioning
confidence: 99%